PENGARUH EARNING PER SHARE, TOTAL ARUS KAS DAN LABA BERSIH TERHADAP HARGA SAHAM (STUDI EMPIRIS PADA PERUSAHAAN PROPERTY SEKTOR REAL ESTATE PERIODE 2018 – 2022 YANG TERDAFTAR DI BEI) - Fajar Idrus Saifulloh .; Riska Damayanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research aims to determine (1) the effect of Earning Per Share, Total Cash Flow, and Net Income simultaneously on Stock Prices in real estate sector property companies listed on the IDX 2018 - 2022, (2) the effect of Earning Per Share on Stock Prices in real estate sector property companies listed on the IDX 2018 - 2022, (3) the effect of Total Cash Flow on stock prices in real estate sector property companies listed on the IDX 2018 - 2022, (4) the effect of Net Income on Stock Prices in real estate sector property companies listed on the IDX 2018 - 2022. The research type is quantitative and the population in research using purposive sampling method obtained a sample of 60 financial reports from 12 companies with an observation period of 5 years and the data is processed using E-Views 9. The results of this study indicate that (1) simultaneously Earning Per Share, Total Cash Flow, and Net Income have an effect on Stock Price. (2) Partially Earning Per Share affect the Stock Price. (3) Total Cash Flow affects the Stock Price. (4) Net Income does not affect the Stock Price.